Barriers to hotel entrepreneurship: a sector analysis - Lado-Sestayo, Rubén (2015)
This paper analyzes the impact of the entry barriers existing in a tourist location on the intensity in the entrepreneurial sector hotel Spanish for the period 2005-2011. In particular, we study a sample of 8,992 hotels by means of four models, namely, Poisson, Negative Binomial, Truncated Models and Logistic Regression. Variables used are related to the level of business concentration, the market size, profitability, employment, investment, employees and closures. Main results point the importance of the level of market concentration as a competitive factor influencing negatively on new ventures. Also, it should also be stressed the positive effect exerted by market size